Numerical analysis on stall suppression of a NACA 0012 airfoil by use of burst control plates - Chhetri, Ashim; Bhattrai, Sudip (Journal of Innovations in Engineering Education, 2022)
Stall suppression is vital during takeoff, maneuver, and landing. Burst Control Plates (BCPs) suppress stall by creating vortices at the leading edge. To suppress stall on NACA 0012 (National Advisory Committee for Aeronautics) airfoil, rectangular cross-section BCPs of a constant height 0.005c and of five different widths (0.008c, 0.016c, 0.024c, 0.032c and 0.040c) are numerically analyzed at four different positions ( 0.045c, 0.05c, 0.07c and 0.1c) on airfoil using ANSYS FLUENT software with transition SST model. For this study airfoil of 200mm chord length(c) at Reynolds number (Re) 1.3 x105 is used. Coefficient of lift (CL), coefficient of drag (CD), and coefficient of pressure (CP) are studied at different angles of attack (α ) for various configurations. BCPs of thickness 0.032c and 0.040c located at 0.045c and 0.05c, suppressed stall by 4°. Other configurations suppressed stall by 2°. Stall suppression by BCP at 0.045c of a thickness 0.032c is found to be the most effective among various configurations.